Conditions giving rise to intense visible room temperature photoluminescence in SrWO4 thin films: the role of disorder - Orhan, E.; Anicete-Santos, M.; Maurera, MAMA; Pontes, F. M.; Paiva-Santos, C. O.; Souza, A. G.; Varela, José Arana [UNESP]; Pizani, P. S.; Longo, Elson [UNESP] (Elsevier B.V., 2005)
The nature of intense visible photoluminescence at room temperature of SrWO4 (SWO) non-crystalline thin films is discussed in the light of experimental results and theoretical calculations. The SWO thin films were synthesized by the polymeric precursors method. Their structural properties have been obtained by X-ray diffraction data and the corresponding photoluminescence (PL) spectra have been measured. The UV-vis optical spectra measurements suggest the creation of localized states in the disordered structure. The photoluminescence measurements reveal that the PL changes with the degree of disorder in the SWO thin film. To understand the origin of visible PL at room temperature in disordered SWO, we performed quantum-mechanical calculations on crystalline and disordered SWO periodic models. Their electronic structures are analyzed in terms of DOS, hand dispersion and charge densities. We used DFT method with the hybrid non-local B3LYP approximation. The polarization induced by the symmetry break and the existence of localized levels favors the creation of trapped holes and electrons, giving origin to the room temperature photoluminescence phenomenon in the SWO thin films. (c) 2004 Elsevier B.V. All rights reserved.
Keywords: ab initio calculations; photoluminescence; thin films